Neurophysiological patterns of ulnar nerve neuropathy in leprosy reactions - Garbino, J. A.; Naafs, B. [UNESP]; Ura, S.; Salgado, M. H. [UNESP]; Virmond, M. (Lepra, 2010)
Background: Leprosy neuropathy, despite being primarily demyelinating, frequently leads to axonal loss. Neurophysiological examination of the nerves during Type 1 (T1R) and Type 2 reactions (T2R) may give some insight into the pathophysiological mechanisms.Methods: Neurophysiological examinations were performed in 28 ulnar nerves during a clinical trial of steroid treatment effectiveness, 19 patients with T1R and nine with T2R. The nerves were monitored during a period of 6 months; there were eight assessments per nerve, for a total of 224 assessments. Nine neurophysiological parameters were assessed at three sites of the ulnar nerve. The compound motor action potential amplitudes elicited at wrist, elbow and above, as well as the conduction velocity and temporal dispersion across the elbow, were chosen to focus on the changes occurring in the parameters at the elbow tunnel.Results and Conclusion: Neurophysiological changes indicating axonal and demyelinating processes during both T1R and T2R were detected across the elbow. Changes in demyelination, i.e. a Conduction Block, as a primary event present during T2R, occurring as an acute phenomenon, were observed regularly; in T1R Temporal Dispersion, a subacute phenomenon, was seen. During treatment remyelination occurred after both types of reactions.